A Hunter’s Moon: the Effect of Moon Illumination on Outdoor Crime - Stolzenberg, Lisa (American journal of criminal justice, 2017)
We use National Incident-Based Reporting System (NIBRS) data and an AutoRegressive Integrative Moving Average (ARIMA) study design to investigate the effect of moon illumination on reported crime occurring outdoors between the hours of 10 pm to 2 am in 13 U.S. states and the District of Columbia. Prior research analyzed a confounded dependent variable that amalgamated indoor and outdoor crimes. This situation is problematic in that there is little reason to speculate a relationship between moon illumination and indoor crime because artificial illumination is used within dwellings. Findings show that while moon illumination has little influence on total crime and indoor crime, the intensity of moonlight does have a substantive positive effect on outdoor criminal activity. As moon illumination intensifies, outdoor crime increases markedly. Plausible explanations for this relationship are discussed.